Apigenin ameliorates di(2-ethylhexyl) phthalate-induced ferroptosis: The activation of glutathione peroxidase 4 and suppression of iron intake. (June 2022) - Han, Dongxu; Yao, Yujie; Chen, Lu; Miao, Zhiying; Xu, Shiwen
Abstract: Di(2-ethylhexyl) phthalate (DEHP) is a widely artificial persistent organic pollutant, the contamination of which infiltrates daily human life from many aspects, imperceptibly causing damage to multiple organs in the body, including the liver. Apigenin (APG) is widely distributed in vegetables and fruits and can relieve or prevent the injuries caused by exogenous chemicals through various pharmacological effects, such as antioxidant effects. To investigate the mechanism of DEHP-induced liver injury and the antagonistic effects of APG, we treated AML12 cells with 1 mM DEHP and/or APG. Ultrastructural morphology analysis indicated that DEHP induced typical ferroptosis-like damage. In addition, we found that DEHP exposure induced ferroptosis by enhancing reactive oxygen species (ROS) levels, disrupting iron homeostasis and lipid peroxidation, and regulating the expression of ferroptosis-related genes. Notably, supplementation with APG significantly inhibited these abnormal changes, and molecular docking further showed evidence of the activating effects of APG ligand on glutathione peroxidase 4 (GPX4). These results demonstrated that the protective effects of APG on DEHP-induced ferroptosis were achieved by activating GPX4 and suppressing intracellular iron accumulation. This information not only adds to DEHP toxicological data but also provides a basis for the practical application of APG. Graphical abstract: These results documented that the protective effects of APG on DEHP-induced ferroptosis were achieved by activating GPX4 and suppressing intracellular iron accumulation. Image 1 Highlights: DEHP exposure caused oxidative stress and enhanced iron content in AML12 cells. DEHP exposure induced ferroptosis in AML12 cells. APG activated GPX4 activity and suppressed iron uptake. APG alleviated DEHP-induced ferroptosis in AML12 cells.